Evaluating of EFL Online Learning on Islamic Higher Education During Pandemic Era - Muhammad Nafi Annury; Adrovvy Jonathan; Musthofa Musthofa (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
The outbreak of Covid-19 brings a new paradigm of conducting the teaching-learning process literally. There is a shifting learning activity from traditional into the recent one. Online learning becomes common sense while doing all the activities supporting the learning process. This recent case study aimed to explore the EFL adult learners’ perceptions and experiences while in online learning classes during the pandemic era. This recent qualitative case study examined the perceptions and experiences of EFL adult learners during their two-year participation in online classes. This qualitative case study was based on Maslow’s theoretical framework. There were a hundred students of EFL at UIN Walisongo Semarang as the participants of this study. They were asked to respond to their perceptions and experiences while conducting online learning via Google form. Questionnaires and semi-structured interviews were used to collect data, and template analysis was used to document the students' experiences taking part in the research. The researchers employed SPSS 21 to analyze the data taken from the questionnaire. It shows that 6% of participants disagreed with implementing online learning. On the other hand, 10.5% of participants strongly agreed with online learning conducted during the pandemic era. At last, there were 34.3% who responded that they neither agreed nor disagreed in online learning classes.